2020
DOI: 10.30961/lr.2020.56.3.437
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus-based Analysis of Collocations in Korean Middle and High School English Textbooks

Abstract: This study analyzed collocations in Korean middle and high school English textbooks based on the 2015 revised national curriculum. All 1,718 nouns from the curriculum wordlist were selected as node words and paired with their collocates statistically verified using a billion-word reference corpus to better represent the existing lexical syllabus. The analysis revealed that collocation density was higher in the textbooks, with readers encountering one collocation per 16-17 words. However, collocations in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 33 publications
1
6
3
Order By: Relevance
“…Overall, the collocations of all subtypes in the textbooks are more repetitive than their counterparts in the reference corpus. The result is conflicting with previous studies which have shown that textbooks present insufficient repetition of target words or collocations (Kim, 2020;Koya, 2004;Tsai, 2015;Yu & Renandya, 2021). It is noticed that NNCs are recycled to a greater extent than VNCs and ANCs in the textbook corpus (24.71 for VNCs, 25.08 for ANCs, and 14.56 for NNCs).…”
Section: Repetition Ratecontrasting
confidence: 69%
See 4 more Smart Citations
“…Overall, the collocations of all subtypes in the textbooks are more repetitive than their counterparts in the reference corpus. The result is conflicting with previous studies which have shown that textbooks present insufficient repetition of target words or collocations (Kim, 2020;Koya, 2004;Tsai, 2015;Yu & Renandya, 2021). It is noticed that NNCs are recycled to a greater extent than VNCs and ANCs in the textbook corpus (24.71 for VNCs, 25.08 for ANCs, and 14.56 for NNCs).…”
Section: Repetition Ratecontrasting
confidence: 69%
“…Frankenberg-Garcia et al (2018) found that a threshold of logDice score greater than or equal to 5 works well for identifying lexical collocations. The logDice with a minimum score of 5 is therefore used in this study (Frankenberg-Garcia et al, 2018;Kim, 2020). And the minimum frequency of occurrence for a word combination to be taken to be a collocation was set at 5.…”
Section: Statistical Criteriamentioning
confidence: 99%
See 3 more Smart Citations